2017
DOI: 10.24212/2179-3565.2017v8i2p142-150
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Study on the Antecedents Predicting Organizational Innovation of the Small and Medium Enterprises in Bangladesh

Abstract: Abstract:In the era of global competition, innovation has become a central object to obtain a sustainable future by an organization outrunning their counterparts. Based on the questionnaires survey on Ready-made Garment (RMGs) and small and medium enterprises (SMEs) in Bangladesh, this empirical study aims at finding the impact of transformational leadership (TL), knowledge management (KM), citizenship behavior or positive deviance (PD), and intrinsic motivation (IM) on organizational innovation (OI). Stratifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…TL is the ability to inspire and empower employees to navigate their self-interests for the enhancement of the organisation and to have a profound and extraordinary effect on followers. TL drives individuals towards a desired destiny by displaying personalised behaviour and a shared vision [22,24,29]. A transformational leader empowers them in questioning the status quo and challenges and stimulates them to think outside of the box by engaging them in divergent thinking rather than in being compliant [28].…”
Section: Transformational Leadershipmentioning
confidence: 99%
See 1 more Smart Citation
“…TL is the ability to inspire and empower employees to navigate their self-interests for the enhancement of the organisation and to have a profound and extraordinary effect on followers. TL drives individuals towards a desired destiny by displaying personalised behaviour and a shared vision [22,24,29]. A transformational leader empowers them in questioning the status quo and challenges and stimulates them to think outside of the box by engaging them in divergent thinking rather than in being compliant [28].…”
Section: Transformational Leadershipmentioning
confidence: 99%
“…Very little if any attention is paid to developing countries and Eastern cases [4]. Negligible studies have been conducted in developing and South Asian nations, including Bangladesh [24,25]. The theory of individual creative action focuses on solving an existing problem by combining ability and motivation with creative action [17].…”
Section: Introductionmentioning
confidence: 99%
“…The past few decades have witnessed sweeping changes in the rate of competition, workforce composition and exploitation of information and communication technology (Huang et al , 2016). These remarkable improvements have reshaped our conventional way of doing things, ultimately leading to the competitive warfare of technology (Arad et al , 1997; Abstein et al , 2014; Fan et al , 2017). In such a situation, innovative behavior within the organizations is deemed to be the vital force for realizing competitive edge and out-running the counterparts (Willoughby et al , 2013; Ashkan, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In such a situation, innovative behavior within the organizations is deemed to be the vital force for realizing competitive edge and out-running the counterparts (Willoughby et al , 2013; Ashkan, 2017). Several studies investigated and identified that innovation, inherited or bred by its creative staffs, is the best opportunity an organization has to withstand the competitive journey (Galvin, 2010; Fan et al , 2017; Strobel and Kratzer, 2017). However, innovation requires employees’ creative process engagement (CPE), which refers to the utilization of employees’ talents and creative ingenuity that inherently necessitates their psychological engagement to work (Rejeb et al , 2008).…”
Section: Introductionmentioning
confidence: 99%
“…To continuously improve the companies, research has shown that SMEs are quite active. Recognising, for example, the crucial role of employee creativity, Fan et al ( 2017 ) examine the link between KM, leadership style, behaviour, motivation and innovation among Bangladeshi SMEs. Internal resources can also be utilised to support knowledge sharing, which in turn has a positive impact on innovation in SMEs (Soto-Acosta et al 2014 ).…”
Section: Presentation Of Findingsmentioning
confidence: 99%